Barriers and facilitators to implementing perinatal mental health care in health and social care settings: a systematic review. (June 2021) - Webb, Rebecca; Uddin, Nazihah; Ford, Elizabeth; Easter, Abigail; Shakespeare, Judy; Roberts, Nia; Alderdice, Fiona; Coates, Rose; Hogg, Sally; Cheyne, Helen; Ayers, Susan; ,; et al.
Summary: The improvement of perinatal mental health formed part of WHO's Millennium Development Goals. Research suggests that the implementation of perinatal mental health care is variable. To ensure successful implementation, barriers and facilitators to implementing perinatal mental health services need to be identified. Therefore, we aimed to identify the barriers and facilitators to implementing assessment, care, referral, and treatment for perinatal mental health into health and social care services. In this systematic review, we searched CINAHL, Embase, MEDLINE, and PsycINFO with no language restrictions for primary research articles published between database inception and Dec 11, 2019. Forward and backward searches of included studies were completed by March 31, 2020. Studies were eligible if they made statements about factors that either facilitated or impeded the implementation of perinatal mental health assessment, care, referral, or treatment. Partial (10%) dual screening was done. Data were extracted with EPPI-Reviewer 4 and analysed by use of a thematic synthesis. The protocol is registered on PROSPERO, CRD42019142854. Database searching identified 21 535 citations, of which 46 studies were included. Implementation occurred in a wide range of settings and was affected by individual (eg, an inability to attend treatment), health-care professional (eg, training), interpersonal (eg, trusting relationships), organisational (eg, clear referral pathways), political (eg, funding), and societal factors (eg, stigma and culture). A complex range of barriers and facilitators affect the implementation of perinatal mental health policy and practice. Perinatal mental health services should be flexible and women-centred, and delivered by well trained health-care professionals working within a structure that facilitates continuity of carer. Strategies that can be used to improve implementation include, but are not limited to, co-production of services, implementation team meetings, funding, and coalition building. Future research should focus on implementation barriers and facilitators dependent on illness severity, the health-care setting, and inpatient care.